2019
DOI: 10.5539/elt.v12n3p139
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Study of the Dictionary Use Sub-strategies of English Majors in Saudi Arabia: Dictionary Related Aspects

Abstract: This study explored the sub-strategies Saudi English majors use most when consulting the dictionary. In particular, it looked at the aspects of the dictionary use strategy relevant to the dictionary itself rather than the lookup words (mainly purposes for consulting the dictionary, means of dictionary ownership and type of dictionary consulted). The participants were 90 English major students enrolled in an English undergraduate program at the Department of European Languages at King Abdulaziz University, Saud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…From the obtained research results, it can be said that the need for a dictionary is very urgent. This is also in line with research conducted by which found that dictionaries have a very important role in the language learning process (Alhatmi, 2019;Muslimin & Surjono, 2018;Rahim & Chun, 2017). This study also found that the quality of a dictionary is also very important in order to provide correct and accurate knowledge to students.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…From the obtained research results, it can be said that the need for a dictionary is very urgent. This is also in line with research conducted by which found that dictionaries have a very important role in the language learning process (Alhatmi, 2019;Muslimin & Surjono, 2018;Rahim & Chun, 2017). This study also found that the quality of a dictionary is also very important in order to provide correct and accurate knowledge to students.…”
Section: Resultssupporting
confidence: 91%
“…Considering the important role of vocabulary in developing literacy, it becomes the reason why vocabulary needs to be taught by using an effective teaching media. A dictionary can be selected as one media to enhance students' vocabulary mastery (Alhatmi, 2019;Deng & Trainin, 2020;Q. Li, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They think that the former saves time while the latter wastes time. These findings have aligned with the study of Alhatmi, S. (2019) in which samples have confirmed the easiness of search on electronic dictionaries and faced some difficulties in using a paper dictionary. Concerning the limitation of dictionaries, as stated in ( 12), results show that 46.8% of the students argue that an electronic dictionary is more limited in some features than a paper dictionary.…”
Section: Assessmentsupporting
confidence: 76%
“…One of the most common methods to research dictionary use is perhaps questionnaire research. Many studies in dictionary research (Fallianda 2020, Hojatpanah and Dashtestani 2020, Alhatmi 2019, Abbasi et al 2019, Chotkarnchanawat et al 2017, Aslan 2016, Boonmoh 2010 have employed this method. Although questionnaire survey research can be used as a way of obtaining results from a great number of respondents and has the potential for generating and testing a hypothesis because the large number of respondents can also mean better representation of the whole population, one basic problem associated with this type of survey as discussed by Nesi (2000) is the accuracy of responses.…”
Section: Literature Review: Uncovering Dictionary Usementioning
confidence: 99%
“…This also changes the ways students consult their dictionaries, and internet or online dictionaries have gained popularity among EFL students (Dashtestani 2015). A number of studies (e.g., Fallianda 2020, Alhatmi 2019, Metruk 2017, Aslan 2016, Anongchanya and Boonmoh 2015, Ding 2015 have shown a growing number of online dictionary users in many countries around the world.…”
Section: Introductionmentioning
confidence: 99%